Intergenerational Transmission of Organizational Misconduct: Evidence from the Chicago Police Department - Frake, Justin; Harmon, Derek (Management Science, 2024)
This paper investigates how organizational misconduct is perpetuated through intergenerational transmission. We theorize that early exposure to a subculture of misconduct imprints newcomers with the belief that misconduct is normal, which is then carried by these individuals into managerial positions and passed down to their subordinates. We test this using longitudinal administrative data from the Chicago Police Department from 1980 to 2017. We exploit a lottery that assigns applicants to training cohorts to demonstrate that officers exposed early on to a subculture of misconduct not only engage in more misconduct over their entire careers, but also increase the misconduct of their subordinates after they become managers. We also find that this intergenerational dynamic is stronger when subordinate officers were exposed to a subculture of misconduct themselves, are earlier in their tenure, and have not yet received their annual review from their manager. Taken together, these findings reveal a bottom-up dynamic whereby beliefs about misconduct are developed in an organization’s lowest ranks, carried by these individuals over time, and passed down to future generations. This study expands our understanding of how organizational misconduct is perpetuated as well as offers important policy implications for addressing the problem of police misconduct. This paper was accepted by Lamar Pierce, organizations. Supplemental Material: The online appendix and data are available at https://doi.org/10.1287/mnsc.2022.00580 .